2014
DOI: 10.1002/glia.22712
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells transduced with a lentiviral vector encoding Fgf‐2 promote motor neuron regeneration following sciatic nerve injury

Abstract: Fibroblast growth factor 2 (FGF-2) is a trophic factor expressed by glial cells and different neuronal populations. Addition of FGF-2 to spinal cord and dorsal root ganglia (DRG) explants demonstrated that FGF-2 specifically increases motor neuron axonal growth. To further explore the potential capability of FGF-2 to promote axon regeneration, we produced a lentiviral vector (LV) to overexpress FGF-2 (LV-FGF2) in the injured rat peripheral nerve. Cultured Schwann cells transduced with FGF-2 and added to collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…FGF-2 is expressed in three isoforms that are upregulated after nerve injury (Klimaschewski et al, 2013). FGF-2 18 KDa isoform mainly enhances motor functional recovery with some effects on sensory functional recovery (Allodi et al, 2014;Haastert et al, 2006;Meyer et al, 2015). In accordance with these studies, we found an enhancement only of motor axon regeneration compared to both controls in the MP group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…FGF-2 is expressed in three isoforms that are upregulated after nerve injury (Klimaschewski et al, 2013). FGF-2 18 KDa isoform mainly enhances motor functional recovery with some effects on sensory functional recovery (Allodi et al, 2014;Haastert et al, 2006;Meyer et al, 2015). In accordance with these studies, we found an enhancement only of motor axon regeneration compared to both controls in the MP group.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, a better way to apply NTFs and prolong their presence in close contact with regenerating axons and Schwann cells is still needed to optimize the effects of NTFs on regeneration. In attempts to increase the NTF availability at the site of injury over time, different approaches have been utilized by using repeated injections through catheters (Mcdonald et al, 2003), osmotic minipumps (Hontanilla et al, 2007), binding to extracellular matrix molecules (Sternel et al, 1997;Sakiyama-Elbert et al, 2000;Lee et al, 2003) or to the wall of nerve conduits (Madduri et al, 2010;Piquilloud et al, 2007) and gene therapy (Allodi et al, 2014;Eggers et al, 2013;Haastert et al, 2006). However, these strategies still present some difficulties to reach optimal nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Exactly 24 h after the application, animals were anesthetized and intracardially perfused with 4 % paraformaldehyde. L4 DRGs were harvested and postfixed in paraformaldehyde for 4 h. The samples were preserved in 30 % sacarose solution before being cut at 20 lm thickness in a cryostat (Allodi et al 2014). Systematic selected images of all DRG sections were taken by a camera attached to a fluorescence microscope (Olympus BX51).…”
Section: Axonal Transport Assessment In Vivomentioning
confidence: 99%
“…[16][17][18][19][20][21] Recently, lentiviral (LV) vectors and plasmids have successfully been employed to direct therapeutic gene expression in SCs in rodent peripheral nerves, [22][23][24][25][26] in rodent and human nerve autografts 27 or in SCs transplanted in various types of grafts used to bridge nerve lesions. [28][29][30][31][32][33][34] However, transgene expression following plasmid transfection is short lived, 26 and LV vectors intergrate their genetic information into the host cell genome that could potentially interfere with the function of vital genes or lead to activation of oncogenes. Although the overall risk of LV vector-associated insertional mutagenesis may be low, 35,36 and recent evidence has provided novel data on the requirements to improve the safety of LV vectors, 37 significant safety concerns remain.…”
Section: Introductionmentioning
confidence: 99%